Regulation of apoptosis and replicative senescence in CD8+ T cells from patients with viral infections. (February 2000) - Soares, M.V.D.; Maini, M.K.; Beverley, P.C.L.; Salmon, M.; Akbar, A.N.
Abstract : Activated T lymphocytes are generated during an immune response. The induction of T lymphocyte proliferation is one way in which cell numbers can be controlled. However, once generated, the increased numbers of cells must be removed in order to re-establish cellular homoeostasis within the immune system. In this paper we describe how the numbers of activated T cells can be regulated by two distinct mechanisms, namely apoptosis and replicative senescence. In addition, we suggest that the regulation of cell clearance, as opposed to cell persistence, after an immune response is intimately involved in the generation of immune memory.